Bioinformatic Analysis of the Cytb Gene to Estimate the Domestication Potential of Mahseer Fish Genus Tor spp. - Permadi, Jefri; Sukmarani, Dhuta; Rahayu, Yeni (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The purpose of this study is to estimate the population of fish of the genus Tor as a source of proper domestication. Bioinformatic analysis was carried out by extracting data from the NCBI gene bank and alignment of the Cytb gene sequences using the ClustalW program to further analyze the nucleotide characteristics using MEGA software, determining genetic variation using the dnasp5 software, and using median joining analysis to reveal the relationship between Tor fish haplotypes from different locations. The results obtained from this study show that the haplotype diversity values of fish of the genus Tor spp. in the domesticated farm population and the natural population are still high, namely 0.9 and 0.8, respectively, as well as the occurrence of haplotype groupings based on other population origins. Domestication of Tor genus fish can be sourced from domesticated farms, and the wild is still ideal because the haplotype diversity is still high.